2002
DOI: 10.1124/dmd.30.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-Mediated Active Transport of a Novel Thromboxane A2 Receptor Antagonist [2-(4-Chlorophenylsulfonylaminomethyl)indan-5-yl]acetate (Z-335) into Rat Liver

Abstract: ABSTRACT:To elucidate the transport system by which [2-(4-chlorophenylsulfonylaminomethyl)indan-5-yl]acetate (Z-335) is taken up into the liver, we investigated the uptake characteristics of Z-335 in isolated rat hepatocytes. In addition, we estimated the hepatic uptake of Z-335 in intact rats under steady-state conditions and compared it with the in vitro uptake clearance. Uptake of Z-335 is highly concentrative (cell-to-medium concentration ratios were 21.2 at 0.5 min and 71.7 at 5 min), temperature-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These results indicate that Z‐335 is mainly taken up into liver and is eliminated by metabolism or biliary excretion. We have recently demonstrated that Z‐335 is taken up into hepatocytes by the sodium‐independent active transport system, and that this uptake is inhibited by substrates of organic anion transporting polypeptides (oatps), such as estradiol 17β‐glucuronide, estrone 3‐sulfate, taurocholate, pravastatin, and bromosulfophthalein (BSP) 5. However, the mechanism for biliary excretion of Z‐335 is not clarified.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that Z‐335 is mainly taken up into liver and is eliminated by metabolism or biliary excretion. We have recently demonstrated that Z‐335 is taken up into hepatocytes by the sodium‐independent active transport system, and that this uptake is inhibited by substrates of organic anion transporting polypeptides (oatps), such as estradiol 17β‐glucuronide, estrone 3‐sulfate, taurocholate, pravastatin, and bromosulfophthalein (BSP) 5. However, the mechanism for biliary excretion of Z‐335 is not clarified.…”
Section: Introductionmentioning
confidence: 99%